2013
DOI: 10.1007/s12024-013-9418-6
|View full text |Cite
|
Sign up to set email alerts
|

Giant cell myocarditis associated with amoxicillin hypersensitivity reaction

Abstract: We report a case of sudden unexpected death in an adult woman from florid myocarditis with necrosis, replacement fibrosis, and diffuse infiltration of the myocardium by eosinophils and conspicuous giant cells. Clinical history revealed that 3 weeks prior to death, shortly after commencing antibiotic therapy for the treatment of traumatic wound of a finger, she presented to the emergency room with a hypersensitivity reaction characterized by facial rash with edema and generalized pruritus. She was treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…To date, only 11 concomitant cases of GCM and DIHS, including the present case, have been reported (Table 2). [5][6][7][8][9][10][11][12] The characteristics of these cases showed that the mean age at presentation was 36.7 (range, 18-74) years, of which two were men and nine were women. The medications used were antibiotics (n = 6), anticonvulsants (n = 4), and loxoprofen (n = 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, only 11 concomitant cases of GCM and DIHS, including the present case, have been reported (Table 2). [5][6][7][8][9][10][11][12] The characteristics of these cases showed that the mean age at presentation was 36.7 (range, 18-74) years, of which two were men and nine were women. The medications used were antibiotics (n = 6), anticonvulsants (n = 4), and loxoprofen (n = 1).…”
Section: Discussionmentioning
confidence: 99%
“…Although the relationship between DIHS and GCM has not been elucidated, from a review of previous literature, we found that most of the GCM cases complicated by DIHS developed during steroid tapering after DIHS. [5][6][7][8][9][10][11][12] Herein, we report a case of GCM requiring a biventricular assist device (BiVAD) due to prolonged cardiac standstill after DIHS, and review the literature on concomitant cases of GCM and DIHS.…”
Section: Introductionmentioning
confidence: 99%
“…Etiologic hypotheses include systemic autoimmune diseases [164][165][166][167][168], drug toxicity [169], infections [170][171][172], and complex combination of autoimmunity, infections and drug toxicity [173]. Infections reported in GCM include coxsackie B2 virus [170], parvovirus B19 [171], HCMV [172] and HIV1 infection [173][174][175][176][177][178][179][180][181][182][183][184]. In most cases, GCM is an isolated entity, while in about one-fifth of cases GCM occurs in association with autoimmune/immune-mediated diseases (Table 4.7), infections, drug toxicity, or syndromes such as immune reconstitution inflammatory syndrome (IRIS) in patients undergoing highly active antiretroviral therapy (HAART) against human immunodeficiency virus type 1 (HIV-1) [173,184,185] or even in patients taking common medications such as amoxicillin [183].…”
Section: Giant Cell Myocarditis and Geneticsmentioning
confidence: 99%
“…Infections reported in GCM include coxsackie B2 virus [170], parvovirus B19 [171], HCMV [172] and HIV1 infection [173][174][175][176][177][178][179][180][181][182][183][184]. In most cases, GCM is an isolated entity, while in about one-fifth of cases GCM occurs in association with autoimmune/immune-mediated diseases (Table 4.7), infections, drug toxicity, or syndromes such as immune reconstitution inflammatory syndrome (IRIS) in patients undergoing highly active antiretroviral therapy (HAART) against human immunodeficiency virus type 1 (HIV-1) [173,184,185] or even in patients taking common medications such as amoxicillin [183]. To date, the autoimmune/ immune-mediated hypothesis is the most accredited pathogenic theory supported both by the aforementioned associations with systemic autoimmune diseases (Table 4.7) and by the partial remission of GCM in patients treated with immunosuppression as well as by the non-aggressive occurrence (10-50%) of the disease during immunosuppression treatment in transplanted patients [186,187].…”
Section: Giant Cell Myocarditis and Geneticsmentioning
confidence: 99%
“…Myocarditis is one of the causes of sudden unexpected deaths. The most common form is lymphocytic myocarditis associated with viral infections 1 . Eosinophilic myocarditis is a rare form of myocarditis, characterized by eosinophilic infiltration of the myocardium 2 .…”
Section: Introductionmentioning
confidence: 99%